Julian von Aeclanum - Ad florum liber primus: Text, Übersetzung und Kommentar - Müller, Veronika 19XX- (Vigiliae Christianae, 2022)
"In this volume Veronika Müller examines Julian's work Ad Florum 1, which is both quoted and commented by Augustine in his Contra Iulianum opus imperfectum. For the first time, Ad Florum 1 is offered in continuous text without Augustine's comments, including a German translation and with a commentary. The most important findings are collected in the introduction providing the reader with a compass to the interpretation of the Latin text. With her analysis, Veronika Müller illuminates the literary and philosophical-theological context of Julian's work particularly focusing on Julian's rhetorical-argumentative approach"--